Comparison of clinical outcomes between use of overexpanding an undersized versus nominal‐sized SAPIEN 3 ultra transcatheter heart valve in patients with borderline annulus area. Issue 3 (28th July 2022) - Basman, Craig; Kodra, Arber; Pirelli, Luigi; Mustafa, Ahmad; Wang, Denny; Li, Angela; Rahming, Hamfreth; Lannan, Lucille; Schultz, Emily; Chaudhary, Richard; Arnone, Paley; Liu, Shangyi; et al.
Abstract: Background: For patients with borderline annulus areas that fall between two valve sizes, overinflating a smaller balloon‐expandable transcatheter heart valve (THV) may be preferable to nominal sizing of a larger THV. Objectives: To evaluate the outcomes of nominal preparation versus over‐expanding an under‐sized SAPIEN 3 Ultra (S3U) transcatheter heart valve (OE‐THV) in cases with borderline annuli. Methods: 958 patients that underwent TAVR with the S3U at four high‐volume TAVR centers between January 2017 and December 2020 were retrospectively reviewed. 336 patients were identified as borderline annuli size, of which 146 (44%) received OE‐THVs and 190 (56%) received nominal‐sized THVs. The primary composite endpoint included: in‐hospital mortality, aortic injury, moderate/severe paravalvular leak (PVL), permanent pacemaker implant (PPM), stroke, or conversion to surgery. Results: Baseline characteristics were similar except for a larger percentage of females in the OE‐THV (53.42% vs. 42.11%, p = 0.04). TAVR with OE‐THV resulted a reduction in the primary composite endpoint (13.69% vs. 22.63%, p = 0.04). On subgroup analysis, there was no difference between 20 mm OE‐THV versus 23 mm nominal or 23 mm OE‐THV versus 26 mm nominal, but there was a reduction in the primary composite endpoint in patients with larger annuli that received a 26 mm OE‐THV compared to the 29 mm nominally sized THV (9.7% vs. 27.4%, p = 0.02). At 1 month and 1 year follow‐up, there was no significant difference in mortality, PVL rates, NYHA class, and/or KCCQ score. Conclusion: Overinflating a smaller‐sized S3U THV may be a safer option in comparison to nominal sizing in patients with borderline annular area.